Effect of substrate on the structural transformation and optical properties of Zn1 − xMgxO thin films grown by pulsed laser deposition. (15th March 2018) - Bellarmine, F.; Senthil Kumar, E.; Ramachandra Rao, M.S.
Abstract: Pulsed laser deposited Mgx Zn1 − x O films grown on sapphire substrates exhibited wurtzite hexagonal structure at lower Mg concentrations (x < 0.20), whereas use of MgO substrates promotes cubic rocksalt structure. For x ≥ 0.20, single-phase cubic ZnMgO thin films with 〈200〉 orientation were realized on MgO substrates. However, the films grown on sapphire substrates exhibited single-phase cubic structure with 〈111〉 orientation only when x ≥ 0.4. We show that the optical bandgap of wurtzite ZnMgO films can be tuned from 3.27 eV to 3.80 eV. On the other hand cubic ZnMgO films exhibited larger bandgap values as high as 5.99 eV. Graphical abstract: Image 1